Ectopia lentis et pupillae: the genetic aspects and differential diagnosis. Issue 11 (November 1991) - Colley, A; Lloyd, I C; Ridgway, A; Donnai, D
Abstract : Two sib pairs and a fifth child are described with autosomal recessive ectopia lentis et pupillae. Patients with this disorder need regular ophthalmic review, but do not have the skeletal and metabolic complications associated with other syndromes with ectopia lentis.